1995
DOI: 10.1097/00000542-199502000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Effects of Propofol in Hamsters with Hypertrophic Cardiomyopathy 

Abstract: Propofol did not modify intrinsic myocardial contractility in normal hamsters, and no significant differences were observed between normal and cardiomyopathic hamsters. These results may be useful because, unlike propofol, most anesthetics decrease myocardial contractility. Nevertheless, indirect cardiac effects of propofol may be more important than its direct cardiac effects in patients with impaired cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Propofol also has some direct negative inotropic effect on the heart, but studies have shown that the net effect on myocardial contractility is insignificant in clinically used concentrations. 6 All of the potent volatile anesthetic agents are myocardial depres sants, and for this reason, high concentration of these agents is best avoided. Among the intravenous induction agents, etomidate is preferred as it causes least cardiovas cular depression.…”
Section: Dilated Cardiomyopathy and General Anesthesiamentioning
confidence: 99%
“…Propofol also has some direct negative inotropic effect on the heart, but studies have shown that the net effect on myocardial contractility is insignificant in clinically used concentrations. 6 All of the potent volatile anesthetic agents are myocardial depres sants, and for this reason, high concentration of these agents is best avoided. Among the intravenous induction agents, etomidate is preferred as it causes least cardiovas cular depression.…”
Section: Dilated Cardiomyopathy and General Anesthesiamentioning
confidence: 99%
“…Second, species differences may exist in the myocardial effects of propofol and the characteristics of coronary circulation. Some reports demonstrated that the effect of propofol on diseased myocardium was not modified in cardiomyopathic hamsters [6], in hypertrophic rabbit heart [4], or in human myocardium isolated from patients with congestive heart failure [5]. In contrast, Hebbar et al reported that porcine myocytes in congestive heart failure were more sensitive than normal myocytes to the negative inotropic effect of propofol [7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to evaluate the cardiovascular effects of propofol in this situation. Propofol has been reported to have no direct negative inotropic effect at therapeutic concentrations in normal myocardium [1][2][3]; however, the effect of propofol on contractility in chronic diseased myocardium is controversial [4][5][6][7]. Furthermore, there have been few reports concerning the effect of propofol on myocardial contractility in acute heart failure, such as that occurring in ACS.…”
mentioning
confidence: 99%
“…This is consistent with previous studies which indicated that propofol does not inhibit myocardial contractility at clinical dosages. 11,12) However, propofol shows negative inotropic effects in a dose-dependent manner at higher concentrations. 13,14) This effect is mainly due to the inhibition of cardiac L-type calcium currents.…”
Section: Discussionmentioning
confidence: 99%